Factors that influence transition to advanced roles by RN to BSN nurses, in three selected hospitals of Central-Uganda - John Baptist Asiimwe; Mercy Muwema; Karen Drake (BMC, 2019)
Abstract Background Despite the global rise in the number of nurses upgrading from Registered Nursing (RN) to a Bachelor of Science in Nursing (BSN), studies have indicated that successful role transition is difficult once the nurses return to their previous workplaces. Guided by the Transitional Theory, this study investigates the factors that influence the transition from basic to advanced roles among RN to BSN nurses in Uganda, Africa. Methods This study employed a descriptive correlational design. Using convenience sampling, fifty-one (51) RN to BSN nurses completed the semi-structured questionnaires. Results All the study participants (100%) described themselves as having transitioned from RN to BSN role. In bivariate linear regression, personal factors that were found to predict successful role transition included holding a managerial role, being aware and prepared for the role transition, and positive role transition experiences. Role transition motivators that predicted successful role transition included: job promotion, internal desire for self-development, and career development. One community factor - that is the support of doctors/physicians during the RN to BSN transition - predicted unsuccessful role transition. Societal factors deterring successful role transition included lack of support from other colleagues and the perception that BSN learning was not applicable to the RN clinical setting. In multivariate linear regression, only sub-scales of personal factors such as advanced skills mastery and positive personal experiences predicted successful role transition. Conclusion The study suggests that personal factors influence successful role transition more than external factors.